y=x+2分之x-3的反函数是x=1-y分之3+2y;请问它解的过程解法是什么?
1个回答
y=(x-3)/(x+2)
-->y*(x+2)=x-3
-->x*y+2y-x+3=0
-->x*(y-1)=-2y-3
-->x=(2y+3)/(1-y)
相关问题
3分之2(x-y)-4分之x+y=-12分之1 3(x+y)-2(2x-y)=3解方程组
{2分之x+y=5分之3x+3y,2分之x+y=1 解方程
Y=x-2分之3x+1的反函数,
解方程组.x+y分之2-x-y分之1=3,x+y分之3+x-y分之4=10.
解方程组2分之x+y+4分之x-y=-3 2分之x+y-4分之x-y=1
2(x+2y)-3x=-1,2分之x+y-3分之x-2y=2 解方程组.
解方程解方程组3x-2y分之4 + 2x-5y分之3=10;3x-2y分之5 - 2x-5y分之2=1
解方程组:x+y分之2+x-y分之3=6(1) 2(x+y)-3x+3y=24
解方程组 1.3x+2y=21,2x-y=14 2.4分之x+3分之y=7,3分之x+2分之y=8
解方程组{3分之2x-4分之3y=2分之1{4(x-y)-3(2x+y)=17